2022
DOI: 10.1073/pnas.2110406119
|View full text |Cite
|
Sign up to set email alerts
|

Narratives imagined in response to instrumental music reveal culture-bounded intersubjectivity

Abstract: The scientific literature sometimes considers music an abstract stimulus, devoid of explicit meaning, and at other times considers it a universal language. Here, individuals in three geographically distinct locations spanning two cultures performed a highly unconstrained task: they provided free-response descriptions of stories they imagined while listening to instrumental music. Tools from natural language processing revealed that listeners provide highly similar stories to the same musical excerpts when they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 42 publications
4
35
1
Order By: Relevance
“…We found that the probability of human-annotated boundaries coinciding with acoustic feature changes was higher than the rate expected because of chance, but the relationship was complex: Although changes in each of the individual acoustic feature types were significantly related to the occurrence of annotated boundaries, none of these features came close to fully predicting the annotated boundaries, and although the majority of annotated boundaries occurred at time points where two or more acoustic features changed, some annotated boundaries did not correspond to changes in any of the acoustic features that we tracked. This adds further support to the possibility that boundaries marking the shift between large-scale segments within the DMN and auditory areas could be driven by a complex shift in a combination of the acoustic properties and/or possibly emotional (Daly et al, 2015) or narrative (Margulis et al, 2019(Margulis et al, , 2021McAuley et al, 2021) changes within the excerpts, rather than a change in a single feature.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…We found that the probability of human-annotated boundaries coinciding with acoustic feature changes was higher than the rate expected because of chance, but the relationship was complex: Although changes in each of the individual acoustic feature types were significantly related to the occurrence of annotated boundaries, none of these features came close to fully predicting the annotated boundaries, and although the majority of annotated boundaries occurred at time points where two or more acoustic features changed, some annotated boundaries did not correspond to changes in any of the acoustic features that we tracked. This adds further support to the possibility that boundaries marking the shift between large-scale segments within the DMN and auditory areas could be driven by a complex shift in a combination of the acoustic properties and/or possibly emotional (Daly et al, 2015) or narrative (Margulis et al, 2019(Margulis et al, , 2021McAuley et al, 2021) changes within the excerpts, rather than a change in a single feature.…”
Section: Discussionmentioning
confidence: 67%
“…Indeed, some evidence already exists for shared neural resources for processing music and language (Asano, Boeckx, & Seifert, 2021;Lee, Jung, & Loui, 2019;Jantzen, Large, & Magne, 2016;Peretz, Vuvan, Lagroi, & Armory, 2015;Tillmann, 2012;Koelsch, 2011;Patel, 2011;Fedorenko, Patel, Casasanto, Winawer, & Gibson, 2009;Tallal & Gaab, 2006;Koelsch et al, 2002). This connection between music and language is also supported by recent behavioral studies showing that instrumental music has the capacity to drive shared narrative engagement across people (Margulis, Wong, Turnbull, Kubit, & McAuley, 2021;McAuley, Wong, Mamidipaka, Phillips, & Margulis, 2021;Margulis, Wong, Simchy-Gross, & McAuley, 2019). In the current work, we test the hypothesis that DMN regions, which represent high-level event structure in narratives, also play a critical role in representing high-level event structure in music.…”
Section: Introductionmentioning
confidence: 58%
“…This is not to say that experience does not shape listeners’ understanding of music. Experience shapes many facets of musicality, from musical preferences (Peretz et al, 1998; Schellenberg et al, 2008), to the enculturation of extramusical associations (Margulis et al, 2022). Experience can even exert subtle influences on our perception of basic structures of rhythm (Drake & Ben El Heni, 2003) and pitch (Jacoby et al, 2019); the influences need not be limited to musical experience, as shown by the effect of linguistic experiences on music processing (Liu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This sensitivity may be revealed in explicit discussions of music or in the thoughts and images that are evoked by music. For example, the stories that people imagine while listening to previously unfamiliar excerpts of music can be remarkably consistent within cultures (Margulis, 2017; Margulis et al, 2019; McAuley et al, 2021; Margulis et al, 2022).…”
Section: Toward a Music Appreciation Frameworkmentioning
confidence: 99%